Potential Adsorption of Heavy Metal Ions by Eugenol Compounds and Derivatives through Ion Imprinted Polymer - Muhammad Cholid Djunaidi; Khabibi Khabibi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Research on the potential of Ion Imprinted Polymer (IIP) selective adsorption of heavy metals using eugenol compounds and their derivatives has been carried out. Isolation and synthesis of eugenol derivatives with metal selective active groups and their use as selective metal carriers have been carried out with satisfactory results. Carrier effectiveness can still be improved by methods that focus on the target molecule recognition model. This adsorption method is called Ion Imprinted Polymer (IIP). The main components of IIP are functional monomers, crosslinkers, and target molecules. The use of acrylamide and its derivatives as functional monomers is useful with a lot of success achieved but also invites danger because it includes carcinogenic substances, a nerve poison, and so on. Moreover, the N group, which is an active acrylamide group, and its derivatives are only selective towards borderline metals (HSAB theory). Alternatives that are safe and can increase their selectivity are therefore needed. Eugenol, with its three potential functional groups, is believed to be able to replace the function of acrylamide and its derivatives that can even increase the effectiveness of IIP. The purpose of this study is to determine the potential of eugenol derivatives as selective adsorbents through the IIP method. This synthesis of IIP involved the use of basic ingredients of eugenol and its derivatives (polyeugenol, EOA, polyacetate). Each base material is contacted with a metal template then crosslinked with three kinds of crosslinking agents, namely EGDMA, DVB, and bisphenol. IIP is formed after the metal template is released using acid/HCl. The outcomes obtained demonstrate that the IIP method is able to increase the metal adsorption capacity and that the IIP method for metals is largely determined by the release of metals, which will form a hole for metal entry through adsorption. Poly-Cd-DVB, Eug-Cr-DVB, Poly-Cu-bisphenol, Polyacetate -Cr-DVB are polymer materials that have the potential to make up an IIP.